2008
DOI: 10.1143/jjap.47.2636
|View full text |Cite
|
Sign up to set email alerts
|

On the Characteristics and Spatial Dependence of Channel Thermal Noise in Nanoscale Metal–Oixde–Semiconductor Field Effect Transistors

Abstract: The physical origin of the channel thermal noise in nanoscale RF metal–oxide–semiconductor field effect transistors (MOSFETs) is characterized based on an analytical noise model, which takes into account velocity saturation, channel length modulation, and carrier heating effect. These short channel effects increase the channel thermal noise compared with predicted noise from long-channel theory. Among the three effects, the channel length modulation is found to be the most important short channel effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…For decreasing channel length, as expected, the drain current noise of Equation ( 8) increases, while the induced gate noise of Equation ( 11) and the correlation noise of Equation ( 12) decrease owing to the cubic and quadratic dependence of I d , respectively. This is consistent with other noise models and measured results [2][3][4][5][6][7].…”
Section: Thermal Noise Modelsupporting
confidence: 92%
See 3 more Smart Citations
“…For decreasing channel length, as expected, the drain current noise of Equation ( 8) increases, while the induced gate noise of Equation ( 11) and the correlation noise of Equation ( 12) decrease owing to the cubic and quadratic dependence of I d , respectively. This is consistent with other noise models and measured results [2][3][4][5][6][7].…”
Section: Thermal Noise Modelsupporting
confidence: 92%
“…The RBF-IANN consists of the same structure as the RBF-DANN in the neural network. Note that the RBF-IANN has an input parameter of the normalized spatial distribution of the local current noise source x/L, incorporating the physical origin of the high frequency [7]. Numerical calculations are performed with v sat = 0.9 × 10 7 cm/s, k bulk = 1.2, T = 300 K, µ e f f = 550 cm 2 /Vs.…”
Section: Model Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, excess noise factor NTNOI is expressed as NTNOI = (L eff /L c ) 2 . This result is in accordance with the result of [6], which showed that the channel-length modulation is critical short-channel effect to explain excess channel thermal noise in short-channel MOSFET. L c can be obtained from the result of [7, eq.…”
Section: Accurate Channel Thermal Noise Modeling In Bsim4supporting
confidence: 92%